Dakwah Melalui Humor ala Gus Iqdam - Muh Ruslan Zamroni (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research discusses the study of comedy in preaching from one of the prominent preachers from Java who is currently famous in cyberspace, namely Gus Muhammad Iqdam. The use of comedy in preaching is something that many preachers do either through the pulpit directly or through internet media such as YouTube. Comedy can attract the attention of preachers because it can create a pleasant atmosphere in their preaching activities. Therefore, it is important for a preacher to regulate the use of comedy in each of his preaching activities. Gus Muhammad Iqdam is famous for every joke in his da'wah activities, which are mostly related to everyday events experienced by the community. Not infrequently he also brings sarcastic comedy and even smart comedy by using sentences that are very appropriate to the audience present. This research is a qualitative type through a content analysis approach. The source of this research was obtained from live da'wah videos on the Gus Iqdam Official Youtube channel as well as from articles, books, and other references related to this research. The results of this study indicate that one of the effective strategies to overcome listeners' boredom in da'wah activities is to use humor, because humor can be an attraction for a da'i and bring a pleasant atmosphere in his preaching. This is done to avoid the impression of monotony in preaching, it is necessary to add interesting elements, both when conveying preaching orally and in writing.